Studi Penggunaan Antibiotika pada Neonatus Di NICU RSAL Dr. Ramelan Surabaya - Victoria Yulita Fitriani (Journal of Tropical Pharmacy and Chemistry, 2011)
ABSTRACT Neonatal sepsis and nosocomial infection are the most common diagnosis of neonatal infections. Selections of antibiotics in neonatal infection should be based on type of bacteria, antibiotics dose and safety in neonates. The aim of this study was to explored type of antibiotics used in Neonatal Intensive Care Unit. Researchers conducted a prospective study of antibiotics used at Dr. Ramelan Navy Hospital neonatal intensive care unit Surabaya. From November 26th 2007 to January 26th 2008, 94 patients (5 preterm neonates and 89 term neonates) were included in this study. Demographic data, antibiotics used, relevant medical histories, laboratory data was recorded prospectively at the wards. Charts for all cases were reviewed. Early antibiotic use was defined as therapy within 72 hours of life. The most frequently used empiric antibiotic regimens were ampicillin sulbactam with gentamicin (60.2%), ampicillin sulbactam (30.1%), ceftriaxone (6.5%), ampicillin sulbactam with amikacin (1.1%), ampicillin sulbactam with ceftriaxone (1.1%), gentamicin with ceftriaxone (1.1%). Late antibiotic events also occurred in neonates. Fourty eight point four percent of late antibiotics events were used of ceftriaxone. Antibiotics are prescribed appropriately but earlier discontinuation or switches, which may be complicated either by the inability to confirm causative organism or patient’s condition that showed no improvement, should be practiced. Key words: Neonatus, antibiotic ABSTRAK Diagnosa infeksi pada neonatus umumnya berupa sepsis neonatorum dan infeksi nosokomial. Pemilihan antibiotika pada kondisi tersebut perlu didasarkan kepada jenis bakteri yang umumnya terlibat, dosis antibiotika dan tingkat keamanan pada neonatus. Penelitian ini bertujuan untuk mengeksplorasi jenis antibiotika yang digunakan pada pasien neonatus. Penelitian ini merupakan penelitian prospektif dengan melakukan pengamatan secara langsung selama 3 bulan di NICU RSAL Dr. Ramelan Surabaya. Peneliti mengobservasi pasien secara langsung dan mengambil data pemakaian antibiotika melalui rekam medik. Semua pasien neonatus yang menjalani rawat inap di NICU periode (Oktober – Desember 2007) disertakan sebagai sampel penelitian. Hasil penelitian di dapat antibiotika untuk penanganan tahap awal yang sering digunakan adalah kombinasi ampisilin sulbaktam dengan gentamisin (60.2%), ampisilin sulbaktam (30.1%), ceftriaxonee (6.5%), kombinasi ampisilin sulbaktam dengan amikasin (1.1%), kombinasi ampisilin sulbaktam dengan ceftriaxonee (1.1%), kombinasi gentamisin dengan cetriaxone (1.1%). Antibiotika untuk penanganan tahap akhir adalah ceftriaxonee (48.4%), kombinasi ceftriaxone dengan amikasin (25.6%), amikasin (9.3%), ampisilin sulbaktam (4.7%), kombinasi ceftriaxone dengan gentamisin (4.7%), kombinasi ampisilin sulbaktam dengan gentamisin (4.7%), kombinasi ampisilin dengan amikasin (4.7%), kombinasi ampisilin sulbaktam dengan amikasin (4.7%), kombinasi ceftriaxone dengan amikasin (4.7%). Kata Kunci: neonatus, antibiotika